Mulato II (Brachiaria sp.) - Joao Vendramini; Brent Sellers; Lynn E. Sollenberger; Maria Silveira (EDIS, 2011)
Mulato II is a semi-erect perennial apomictic grass that can grow up to 9 ft tall. Brachiariagrasses, including Mulato II, are tropical warm season forages native to Africa and are the most widely grown forages in tropical South America. This revised 4-page fact sheet describes the morphology, region of adaptation and growing season in Florida, recommended production practices, and the results of research into the performance of heifers grazing Mulato. Written by J. Vendramini, B. Sellers, L.E. Sollenberger, and M. Silveira and published by the UF Department of Agronomy, March 2011.